New ecophysiological perspectives on the kelp Macrocystis pyrifera: generating a basis for sustainability in the sub-Antarctic region - Marambio, Johanna; Rodríguez, Juan Pablo; Rosenfeld, Sebastián; Méndez, Fabio; Ojeda, Jaime; Ocaranza, Paula; Bischof, Kai; Mansilla, Andrés (Frontiers in Marine Science, 2023)
These extensive kelps forest are among the most productive and diverse habitats on the planet, playing an important ecological role in marine ecosystems. These habitats have been affected by anthropogenic factors worldwide and directly by environmental variations resulting from climate change. The Magellan ecoregion has the southernmost kelp forests in the world, dominated by the species Macrocystis pyrifera. This species presents high ecophysiological plasticity being able to inhabit heterogeneous environments, characteristic of the fjord and channel systems of the region, and has high ecological, sociocultural, and economic importance for local coastal communities. To understand the ecophysiological acclimation strategies of M. pyrifera, samples from different blades were collected at different depths at four locations in the Magellan Ecoregion: Possession Bay, Skyring Sound, Otway Sound, and Puerto del Hambre seasonally. Abiotic measurements (salinity, temperature, and PAR light) were carried out for each location sampled. Measurements of photosynthetic parameters, Fv/Fm, rETRmax, Ek and α; pigment analysis of Chl a, Chl c, and fucoxanthin; and fecundity analysis of the sporophylls of each population studied were carried out on the M. pyrifera sporophytes. Significant differences were observed between seasons, locality, and depth of blades. Each population generally showed different photoacclimation processes, depending on the local conditions such as salinity values and probably tidal cycles. This is reflected in the photosynthetic, pigment, and fecundity values obtained during this study. The higher Fv/Fm values in all populations during the winter and autumn seasons and the differences in Chl c and fucoxanthin concentration during the winter period in Otway Sound and Puerto del Hambre population suggest the marked seasonal acclimation of M. pyrifera. In addition, the coastal environmental heterogeneity observed in the Magellan ecoregion related to salinity gradients (Skyring Sound) or wide tidal amplitudes (Possession Bay) influences the acclimation strategy of each population of M. pyrifera. Therefore, the characteristics of each population should be considered in order to promote its sustainability in times of social and climate change.